Form‐stable Na2SO4·10H2O‐Na2HPO4·12H2O eutectic/hydrophilic fumed silica composite phase change material with low supercooling and low thermal conductivity for indoor thermal comfort improvement. (20th January 2020) - Fang, Yutang; Su, Jianmin; Tang, Yufeng; Liang, Xianghui; Wang, Shuangfeng; Gao, Xuenong; Zhang, Zhengguo
Summary: In this research, a novel form‐stable composite phase change material (CPCM) based on Na2 SO4 ·10H2 O‐Na2 HPO4 ·12H2 O binary eutectic hydrated salt (EHS) as phase change material (PCM) and porous hydrophilic fumed silica (SiO2 ) as the carrier was prepared via the impregnation method, which is aimed at being integrated into building envelopes for the improvement of indoor thermal comfort and the reduction of building energy consumption. Thereinto, Na2 SiO3 ·9H2 O utilized as the nucleating agent suppressed the supercooling of the EHS enormously. Differential scanning calorimetry (DSC) result and the crystalline phase obtained by X‐ray diffraction (XRD) revealed that the mixture consisting of 20‐wt% Na2 SO4 ·10H2 O and 80‐wt% Na2 HPO4 ·12H2 O exhibited a eutectic melting behavior. Depending on DSC and leakage tests, the optimum amount of SiO2 in CPCM was determined as 30 wt%, which successfully stabilized the shape of the EHS to avoid leaking, simultaneously reduced thermal conductivity, and further facilitated its crystallization. Additionally, scanning electron microscope (SEM) manifested that the EHS was well adsorbed into the mesopores of SiO2 . The obtained CPCM revealed an applicable phase transition temperature (25.16°C), moderate melting enthalpy (142.9 kJ·kg −1 ), negligible supercooling degree (0.24°C), and low thermal conductivity. More importantly, after 200 melting‐solidifying cycles, it displayed an excellent thermal reliability. All these results showed that the CPCM possessed desirable properties for applications.